Unveiling the Dental Connection: A Case Report of Odontogenic Initiating Chronic Suppurative Otitis Media - Gita Khusnul Khatimah; Guntur Surya (Universitas Malahayati Lampung, 2024)
ABSTRACT Chronic suppurative otitis media (CSOM) is a troubling condition that encompasses a range of factors contributing to its etiology. In this context, we present an intriguing and atypical case that adds a novel dimension to the understanding of CSOM. This particular case is marked by its prolonged and treatment-resistant nature, defying conventional medical treatments and prompting us to explore less common etiological pathways. Our case, however, deviates from the norm. It presents a conundrum that led us to investigate an alternative and less explored avenue. During our comprehensive diagnostic evaluation, our attention was drawn to the possibility of a hematogenic infection that may have originated from dental caries. This scenario emerged as the primary candidate for the source of the patient's chronic suppurative otitis media. This intriguing case represents a unique instance of a hematogenic infection stemming from dental caries. The hematogenic pathway, while previously considered uncommon, may be the precipitating factor behind the development of chronic suppurative otitis media in this patient. This perspective widens our understanding of the various potential etiological factors contributing to CSOM and highlights the importance of considering less conventional sources of infection. In the context of otologic disorders, the case we present underscores the necessity of a thorough and holistic diagnostic approach, acknowledging that the origins of such conditions can often be multifaceted and not limited to the conventional causes. Furthermore, this case serves as a reminder for clinicians to maintain a high level of suspicion for atypical etiological pathways when faced with treatment-resistant and persistent manifestations of CSOM. Keywords: Chronic Suppurative Otitis Media, Dental Caries, Odontogenic, Hematogenic